HARMONISASI NILAI AMANAH DAN NGAJENI DALAM PELAYANAN KONSUMEN PADA UMKM DI JAWA TENGAH: Harmonizing the Values of Amanah (Trustworthiness) and Ngajeni (Respect) in Customer Service for MSMEs in Central Java - Putri Purwaningtyas (tesco publisher, 2025)
This study investigates the socio-religious dimensions of contemporary business practices by analyzing the harmonization of Amanah (the Islamic principle of integrity and trust) and Ngajeni (the Javanese cultural ethics of mutual respect) within the Micro, Small, and Medium Enterprises (MSMEs) sector in Central Java, Indonesia. The primary objective is to identify how the integration of these two values influences interaction patterns between entrepreneurs and consumers in cultivating sustainable customer loyalty. Employing a qualitative descriptive method with a transcendental phenomenological approach, data were gathered through in-depth interviews with 17 MSME owners across various sub-cultural regions in Central Java, complemented by direct field observations. The findings reveal that Amanah serves as a fundamental moral anchor that ensures transactional honesty, informational transparency, and promised product quality. Concurrently, the ethics of Ngajeni function as a communicative instrument that prioritizes humanism, humility, and social etiquette (unggah-ungguh). The synergy between these values culminates in a